2020
DOI: 10.1002/smll.202001099
|View full text |Cite
|
Sign up to set email alerts
|

Cu2MoS4 Nanozyme with NIR‐II Light Enhanced Catalytic Activity for Efficient Eradication of Multidrug‐Resistant Bacteria

Abstract: instead of CMS NPs dispersion for the saline and saline + NIR-II groups. 10 min later, infected site of the mice was irradiated by 1064 nm laser (1 W cm −2) for 5 min for saline + NIR-II and CMS + NIR-II groups. The infected area was monitored and photographed daily. At the therapeutic day 16, the infected tissues were homogenized and diluted in saline by ultrasonication. Then, these dilutions (100 µL) were plated on LB agar plates. The number of CFU was counted after incubation for 18 h at 37 °C. At the thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
95
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(95 citation statements)
references
References 56 publications
0
95
0
Order By: Relevance
“…[ 9 , 10 ] Compared with antibiotics, the ROS-based sterilization method can avoid the occurrence of bacterial resistance, therefore, the development of ROS-based antibacterial strategies is very effective and promising [ 11 ]. At present, it has been proved that many nanomaterials with enzyme-like and antibacterial properties, including noble metal nanoparticles [ 12 ], carbon-based nanomaterials [ 13 ], metal oxides [ 11 , 14 ], and metal chalcogenides [ [15] , [16] , [17] ], can eradicate different types of bacteria, even drug-resistant bacteria. Unfortunately, the low catalytic activity of nanozymes greatly limits their antibacterial effects [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 9 , 10 ] Compared with antibiotics, the ROS-based sterilization method can avoid the occurrence of bacterial resistance, therefore, the development of ROS-based antibacterial strategies is very effective and promising [ 11 ]. At present, it has been proved that many nanomaterials with enzyme-like and antibacterial properties, including noble metal nanoparticles [ 12 ], carbon-based nanomaterials [ 13 ], metal oxides [ 11 , 14 ], and metal chalcogenides [ [15] , [16] , [17] ], can eradicate different types of bacteria, even drug-resistant bacteria. Unfortunately, the low catalytic activity of nanozymes greatly limits their antibacterial effects [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Arrhenius equation, the rate of chemical reactions is positively related to temperature [ 22 ]. Starting from the basic principle that raising temperature can accelerate the rate of chemical reactions, increasing temperature of the bacterial infection sites to enhance the catalytic rate of nanozymes is an effective strategy [ 16 ]. Therefore, high temperature can significantly promote the production of ROS, thereby effectively killing bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Wang et al reported a new near-infrared II light-responsive Cu 2 MoS 4 nanozyme with enhanced OXDand POD-like catalytic activities to improve ROS generation for highly efficient killing of bacteria. 138 Although the abovementioned Mo-based nanozymes have been successfully employed to combating bacteria, more effort is required to focus on designing novel Mo-based nanozymes for combating more types of drug-resistance bacteria, promoting long-term wound healing, antibiofilm, and antibiofouling.…”
Section: Combating Bacteriamentioning
confidence: 99%
“…Recently, generating reactive oxygen species (ROS) via chemodynamic, photodynamic, sonodynamic, and enzyme-mimetic materials to combat bacteria has also been explored as promising alternative antibacterial strategies 9 11 . Among diverse ROS generation materials, the enzyme-mimetic catalysts, including nanoliposome 12 , metal-organic frameworks 13 15 , and inorganic materials 16 , 17 , have gained tremendous popularity by catalyzing oxygen and hydrogen peroxide (H 2 O 2 ) to generate ROS via the existing natural pathway. Nevertheless, when treated at a very low concentration, such enzyme-mimetic catalysts present insufficient bacterial killing activities, while utilizing antibacterial materials at high concentrations will always lead to a severe concern on biocompatibility.…”
Section: Introductionmentioning
confidence: 99%